Personality and Career: She's Got What It Takes - Simon Fietze; Elke Holst; Verena Tobsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The female share in management positions is quite low in Germany. The higher the hierarchical level, the fewer women there are in such positions. Men have numerous role models to follow whereas women lack this opportunity: In the executive boards of the top 200 private companies in Germany, only 2.5 percent of members are female. Many studies have focused on the influence of human capital and other "objective" factors on career opportunities. In our study, we go a step further by also looking at the impact of self-reported personality traits on gender differences in career chances. We compare managers and other white-collar employees in Germany's private sector. While bivariate results based on data from the German Socio-Economic Panel (SOEP) in 2005 show that there are significant gender differences in personality traits, multivariate estimations clearly indicate that these differences cannot account for gender differences in career opportunities. Nevertheless, personality traits might indeed play a role, albeit more indirectly: Some of the stronger career effects, such as work experience, long working hours, and labour market segregation, can also reflect differences in personality traits. These might have been influenced at an early stage by a gender-biased environment. Our results strongly stress the need for a gender-neutral environment outside and inside companies in order to enforce equal career opportunities for women and men.
Keywords: J16; M12; 330; personality; gender; career; leadership